Konsep Kepemimpinan dalam Perspektif Islam: Suatu Studi Literatur - Desi Salsabilla Atanaya; Muhammad Abrar; Aos Kuswadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Leadership from an Islamic perspective is not merely about power, but rather a great trust grounded in moral and spiritual values. This article aims to examine the concept of Islamic leadership through a literature review of the Qur'an, hadith, scholarly opinions, and previous research findings. This study employs a qualitative approach using the library research method. Data were obtained from various scholarly sources, particularly journal articles, academic books, and relevant documents discussing leadership in the Islamic context. A total of 25 scientific articles were collected through online databases such as Google Scholar, DOAJ, and Garuda. Of these, 15 articles were selected and analyzed in depth based on criteria of substance relevance, contextual significance, and academic credibility. The findings indicate that justice, trustworthiness, consultation (shura), honesty, firmness, and patience are fundamental principles of Islamic leadership. The exemplary leadership of the Prophet Muhammad (SAW) and the Rightly Guided Caliphs serves as an ideal model combining wisdom, compassion, and responsibility toward the community. These values remain relevant today as ethical foundations in addressing contemporary leadership challenges. Thus, Islamic leadership offers a comprehensive model that integrates professionalism and spirituality.